Early intervention results in lower mortality in patients with cancer hospitalized for metastatic spinal cord compression. (30th January 2017) - Guddati, Achuta Kumar; Kumar, Gagan; Shapira, Iuliana
Abstract : Metastatic spinal cord compression (MSCC) is one of the most dreaded complications of cancer. A Nationwide Inpatient Sample (NIS) from 2000 to 2011 was used to extract data for all in-hospital stays of patients with MSCC using the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes. The usage and timing of radiation therapy and surgical interventions were identified using ICD-9-M codes. These interventions were defined as 'early intervention' if they were provided within the first 48 hours of hospitalization. Multivariable logistic regression was used to examine the factors associated with delays in 'early intervention'. We also examined whether delays in treatment led to worse outcomes in terms of mortality and morbidity. 13 457 patients were admitted with MSCC from 2000 to 2011 who received one or more modalities of treatment. Of these, 5035 (37%) received early intervention. Female gender, private-for-profit hospitals and higher comorbidity index were associated with lower rate of early intervention. In-hospital mortality was lower in the early intervention group (5.0% vs 6.9%, p=0.04). Patients receiving early intervention were discharged home more often (44.2% vs 36.4%, p<0.001) along with lower need of home health services (14.6% vs 18.8%, p=0.004). The length of stay (LOS) was significantly shorter and hospital charges lower in those who received early intervention (LOS: median 6 vs 11 days, p<0.001; charges: $34 354 vs $50 062; p<0.001). The rate of care delivery by early intervention in MSCC is suboptimal. Early treatment results in lower mortality, shorter LOS and higher rates of discharges to home along with lower hospital charges and decreased usage of home healthcare.